Characteristics and trend of distribution of rainfall in Singapore - Ong, Zhiwei. (2009)
In this report, time series analysis and student t-distribution hypothesis test are carried out to determine the rainfall trend pattern in Singapore and the confidence level of this rainfall trend occurring. The objective of this study is to analyze the characteristics and trend of distribution of rainfall in Singapore, and qualitatively evaluate how the trend going to impact on Singapore’s water resource quality.